Developing Augmented Reality-Based Learning Media to Enhance High School Students’ Understanding of Biogeochemical Cycles - Neng Astry Mediana; Lukman Nulhakim; Rudi Haryadi (AL-ISHLAH: Jurnal Pendidikan, 2025)
The complexity of biogeochemical cycles often presents challenges for high school students due to abstract concepts and limited visual learning tools. Augmented Reality (AR) offers an innovative approach to enhance students’ conceptual understanding through interactive and immersive media. This study employed a Research and Development (RD) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). AR-based instructional media focused on biogeochemical cycles was developed and tested on 30 tenth-grade students and 2 biology teachers at SMAN 1 Pontang. Data were collected through pre-tests and post-tests, questionnaires, interviews, and observations, and analyzed using both quantitative and qualitative methods. The findings showed a significant improvement in students’ conceptual understanding, with average scores increasing from 56.30 (pre-test) to 84.70 (post-test), yielding a gain score of 0.65 (moderate to high). Statistical analysis confirmed this improvement as significant (t(29) = 12.45, p 0.001; Cohen’s d = 1.86). Expert validation indicated high feasibility (≥88%), while student and teacher feedback highlighted strengths in interactivity, 3D visualization, and usability. The study demonstrates that AR-based media can effectively support learning of abstract biological concepts by promoting active engagement and visual comprehension. Its application aligns with constructivist learning theories and multimedia learning principles, offering promise for broader use in science education.